Positive Effect of Visual Cuing in Episodic Memory and Episodic Future Thinking in Adolescents With Autism Spectrum Disorder - Anger, Marine; Wantzen, Prany; Le Vaillant, Justine; Malvy, Joëlle; Bon, Laetitia; Guénolé, Fabian; Moussaoui, Edgar; Barthelemy, Catherine; Bonnet-Brilhault, Frédérique; Eustache, Francis; Baleyte, Jean-Marc; Guillery-Girard, Bérengère (Frontiers in Psychology, 2019)
Cognitive studies generally report impaired autobiographical memory in individuals with autism spectrum disorder (ASD), but mostly using verbal paradigms. In the present study, we therefore investigated the properties of both past and future autobiographical productions using visual cues in 16 boys with ASD and 16 typically developing (TD) participants aged between 10 18 years. We focused on sensory properties, emotional properties, and recollection, probing past and future productions for both near and distant time periods. Results showed that the ASD group performed more poorly than controls on free recall, but performed like them when provided with visual cues. In addition, the ASD group reported fewer color details than controls and exhibited recollection difficulties. Our findings reveal the relevance of using visual cues to probe autobiographical memory, and open up new therapeutic perspectives for memory rehabilitation.